Aeolian sediment transport and morphologic change on a managed and an unmanaged foredune. Issue 4 (24th October 2012) - Jackson, Nancy L.; Nordstrom, Karl F.
ABSTRACT Sediment transport and short‐term morphologic change were evaluated at a site where sand fences are deployed and the beach is raked (Managed Site) and a site where these human adjustments are not practiced (Unmanaged Site). Data were gathered across the seaward portion of a low foredune when winds blew nearly shore‐normal at mean speeds 8.9 to 9.3 m s‐1. Data from traps revealed sediment transport rates at unvegetated portions of the foredune crest (40.2 to 43.5 kg m‐1 h‐1) were greater than on the backshore (4.9 to 11.2 kg m‐1 h‐1) due to onshore decreases in surface moisture and speed‐up of the wind passing over the foredune. Data from erosion pins indicate sediment input to the dune was 1.48 m3 m‐1 alongshore at the Managed Site and 1.25 m3 m‐1 at the Unmanaged Site. The Unmanaged Site had deposition at the dune toe, erosion at mid‐slope, and deposition at the crest. Deposition occurred at mid‐slope on the Managed Site near a partially buried (0.58 m high) fence with a porosity of about 65%. Deposition at partially buried wrack on the upper backshore and dune toe at the Unmanaged Site was about twice as great as deposition in this zone at the Managed Site. Results indicate that: (1) the seaward slope of the foredune can be a more important source of sand to the lee of the crest than the beach; (2) wrack near the toe can decrease transport into the foredune; (3) a scour zone can occur on the foredune slope above the wrack line; (4) a fence placed in this location can promote deposition and offset scour, but fences can restrict delivery of sediment farther inland. Evaluation of alternative configurations of fences and strategies for managing wrack is required to better determine the ways that humans modify foredunes. Copyright © 2012 John Wiley & Sons, Ltd.